A case of H. pylori infection presenting as refractory hypothyroidism - Pragya Gupta; Johns T Johnson; Sudarsanababu Lalitha Soumya; Kripa Elizabeth Cherian; Nitin Kapoor; Thomas Vizhalil Paul (Journal of Family Medicine and Primary Care, 2020)
We present the case of a 45-year-old lady with long standing hypothyroidism who was euthyroid on replacement for many years, but stopped responding even to supraphysiological doses of LT4 since the last five years. She complained of abdominal discomfort, bloating, and nausea. She did not have diarrhea or weight loss. Levothyroxine absorption test was done which was suggestive of malabsorption and she was started on triple therapy for H. pylori eradication after confirmation of diagnosis. After 10 days of treatment initiation, she developed symptoms of thyrotoxicosis with her supraphysiological dose of LT4, which was then tapered to a lower dose. Euthyroid state was ultimately achieved with lower doses of LT4 replacement.